Peculiarities of the state of health of water transport workers - N. V. Lazareva; Yu. Ya. Guretskaya; Yu. D. Udalov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
The article analyzes in detail the dynamics of the state of health, the movement of the contingent and the impact of harmful factors on the somatic health of water transport workers in a comparative aspect, depending on the time and degree of exposure to various professional factors.